Discharge aiding agent for oil well fracturing and production method

By double-layer coating of quartz sand with polytetrafluoroethylene and acrylic resin, the problem of degradation of traditional coating materials in high temperature environments is solved, and the temperature resistance and discharge assistance effect of the discharge aid agent are improved.

CN119391397AInactive Publication Date: 2025-02-07ZHENGZHOU DERONG TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411564166.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-07
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Under high temperature environment, the performance of traditional bisphenol A type epoxy resin coating materials decreases, affecting the discharge aid effect of the discharge aid agent.

Method used

The quartz sand is coated with polytetrafluoroethylene and acrylic resin to form a double-layer cladding structure with a solid inner layer and flowing outer layer, improving the temperature resistance and stability of the discharge aid.

Benefits of technology

Maintain the performance of the discharge aid at high temperature, reduce performance degradation, improve the discharge rate and discharge rate of the discharge aid, and extend the effectiveness of the discharge aid in complex environments.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a discharge aiding agent for oil well fracturing and a production method, and relates to the technical field of production of discharge aiding agents. Comprising the following components in parts by weight: 80-95 parts of a basic solution, 0.3-0.9 part of a viscosity modifier, 3-5 parts of a cracking agent, 0.2-0.5 part of a modified dispersant, 6-8 parts of a diethylenetriamine cross-linking agent, 1-3 parts of an acidifying agent, 0.3-0.6 part of a protective agent and 10-30 parts of a modified filler prefabricated solution, the modified dispersant is a lignin modifier obtained by sulfonating and modifying lignin with potassium bisulfite; the modified filler prefabricated liquid is prepared by coating and modifying quartz sand with polytetrafluoroethylene and acrylic resin; the quartz sand is coated with polytetrafluoroethylene and acrylic resin to form a double-layer coating structure with a firm inner layer and a flowing outer layer, so that the mechanical strength, the stability and the high-temperature resistance of the discharge aiding agent are enhanced, and the discharge rate and the discharge aiding rate of the discharge aiding agent are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of drainage aid production, in particular to a drainage aid for oil well fracturing and a production method thereof. Background Art

[0002] CO 2 Oil displacement technology is based on the interaction between carbon dioxide and crude oil. Under the conditions of appropriate pressure, temperature and crude oil composition, carbon dioxide can form a miscible front, and supercritical fluid will extract heavier hydrocarbons from the crude oil and continuously concentrate the gas at the displacement front. As a result, carbon dioxide and crude oil become miscible liquids, forming a single liquid phase, which can effectively displace the formation crude oil to the production well.

[0003] A drainage aid for oil well fracturing is a chemical additive specially designed to improve the drainage efficiency of the drainage aid during oil and gas extraction. In the oil and gas industry, fracturing is a process of injecting a drainage aid containing proppants into the rock cracks of underground reservoirs under high pressure to expand the cracks and increase the permeability of the formation, thereby increasing the production of oil and gas wells. The drainage aid for oil well fracturing optimizes its compatibility and fluidity with the drainage aid. The drainage aid can enhance the ability of the drainage aid to quickly discharge the oil reservoir after completing the purpose of increasing production, reduce damage to the permeability of the reservoir, and thus maintain or restore the production capacity of the oil well.

[0004] In the CO 2 During oil recovery operations, fracturing the oil well can increase the permeability of the oil layer. Adding drainage aids during the fracturing process can ensure the smooth injection and rapid return of the fracturing fluid, reducing damage to the oil layer.

[0005] For example, the Chinese patent with application number CN202410407362.6, a drainage aid for oil well fracturing and a production method, the invention relates to the technical field of drainage aid production, specifically, to a drainage aid for oil well fracturing and a production method. It includes the following components: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidifier, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler prefabricated liquid. Diethylenetriamine is used to achieve covalent bond bonding between the modified dispersant and the modified filler prefabricated liquid to obtain a grafted blend, and the lignin derivative is firmly grafted to the surface of quartz sand by forming covalent bonds; the modified lignin derivative grafted quartz sand not only improves the performance of the fracturing proppant, but also effectively improves the discharge rate and drainage effect of the drainage agent by optimizing the liquid flow characteristics in the formation.

[0006] In the above scheme, the modified filler prefabricated liquid is prepared by coating and modifying quartz sand with bisphenol A epoxy resin, and the discharge aid is applied to CO 2 During oil displacement operations, higher temperatures are usually required to enhance the oil displacement effect. Bisphenol A epoxy resin will experience performance degradation at high temperatures, such as softening and decomposition, which will affect its coating effect and the overall performance of the drainage agent. Summary of the invention

[0007] The embodiments of the present application provide a drainage agent for oil well fracturing and a production method, thereby solving the problem in the prior art that the high temperature environment causes the performance of the coating material bisphenol A epoxy resin to decline, thereby affecting the drainage effect of the drainage agent. Quartz sand is coated with polytetrafluoroethylene and acrylic resin to form a double-layer coating structure with a solid inner layer and a flowing outer layer. The high temperature resistance of the outer layer of polytetrafluoroethylene enables it to maintain good stability and coating effect at high temperatures, thereby improving the temperature resistance of the drainage agent. The inner layer is pre-coated with acrylic resin to form a solid resin layer, which enhances the bonding force between the quartz sand and the outer layer of polytetrafluoroethylene, prevents the coating layer from falling off under high temperature and high pressure, and further improves the stability and drainage effect of the drainage agent.

[0008] The embodiment of the present application provides a drainage aid for oil well fracturing, comprising the following components: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler prefabricated fluid; Wherein, the modified dispersant is a modified lignin obtained by sulfonating lignin with potassium bisulfite; The modified filler prefabricated liquid is prepared by coating and modifying quartz sand with polytetrafluoroethylene and acrylic resin; The base liquid is formed by mixing water and polyoxyethylene octylphenol ether emulsifier; Wherein, the mixing ratio of water and polyoxyethylene octylphenol ether emulsifier is 9:0.3-0.9; The viscosity modifier is any one of carboxymethyl cellulose or guar gum; The breaker is any one of quartz sand, ceramic particles or microspheres; The acidulant is a mixture of one or more of hydrochloric acid, hydrofluoric acid or earth acid; The protective agent is one or more mixtures of butylated hydroxytoluene, isothiazolinone or silver ion antibacterial agent.

[0009] Furthermore, the preparation method of the modified filler pre-liquid is as follows: S2.1, mixing acrylic resin and ethanol in a volume ratio of 3:2, heating until the acrylic resin is molten, stirring evenly, to obtain a flowable acrylic resin solution; Disperse the pretreated quartz sand evenly into the acrylic resin solution, stir for 15-20 minutes at a temperature of 60-80°C and a stirring speed of 200-300rpm, so that the surface of the quartz sand is evenly coated with a layer of acrylic resin to form an inner solid resin coating layer; The coated quartz sand is filtered to remove excess acrylic resin solution, and then placed in an oven and dried at 80-100° C. to solidify the acrylic resin to obtain inner-layer coated quartz sand; S2.2, mixing polytetrafluoroethylene and ethanol in a volume ratio of 3:2, and heating until the polytetrafluoroethylene is molten to prepare a flowable polytetrafluoroethylene solution; 10 parts by weight of the inner-layer coated quartz sand are evenly dispersed into 25 parts by weight of the prepared polytetrafluoroethylene solution, and stirred for 15-20 minutes at a temperature of 65-80°C with a stirring speed of 260-380 rpm by a stirrer to evenly disperse the quartz sand in the polytetrafluoroethylene solution, so that the quartz sand is fully wrapped and infiltrated by the polytetrafluoroethylene solution to obtain a modified filler prefabricated liquid.

[0010] Furthermore, in the preparation of the modified filler preform, the reactions of S2.1 and S2.2 are adjusted, specifically: In S2.1, diethylenetriamine is added to the acrylic resin solution as a crosslinking agent, wherein the amount of the diethylenetriamine crosslinking agent is 8%-10% by weight of the acrylic resin; In S2.2, when coating with the polytetrafluoroethylene solution, the mixture is stirred at a temperature of 60-65° C. and a stirring speed of 200-260 rpm for 10-15 minutes.

[0011] Furthermore, the particle size of the quartz sand in the modified filler includes two types: large particle size and small particle size.

[0012] Furthermore, the particle size range of the large particle size is 0.42-1 mm; the small particle size is 0.10-0.25 mm; and the weight ratio of the large particle size to the small particle size is (1-2):1.

[0013] Furthermore, the modified filler also includes light calcium carbonate.

[0014] Furthermore, the particle size of the light calcium carbonate is 0.8-0.15 mm and the density is 0.5 g / cm³.

[0015] Furthermore, the light calcium carbonate accounts for 12%-18% of the total weight of the modified filler.

[0016] The above-mentioned production method of the drainage agent for oil well fracturing specifically comprises the following steps: S3.1. According to the requirements of the content of each component in the formula of the oil well fracturing agent, weigh the following raw material components in percentage by weight: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler; S3.2, firstly mix the modified dispersant with the diethylenetriamine crosslinking agent, and stir them at a speed of 120-180rpm with a magnetic stirrer for 8-15min to ensure that the two are fully reacted to generate an amine-containing lignin derivative solution; then, mix the amine-containing lignin derivative solution with the modified filler prefabricated solution, and stir them at a temperature of 60-80°C with a magnetic stirrer at a speed of 120-160rpm for 15-30min to generate a lignin derivative solution with an amine functional group, and obtain a grafted blend; S3.3, according to the formula ratio in step S3.1, first add the base liquid into the stirrer, and stir it with the stirrer; at the same time, add the viscosity modifier into the base liquid, and continue to stir so that the viscosity modifier is evenly dispersed in the base liquid; then, under stirring, add the breaker and the acidifier in sequence, and continue to stir until the mixture is evenly mixed to prepare a mixture; S3.4, adding the grafted blend obtained in step S3.2 to the mixture, and evenly dispersing it in the entire drainage agent system by a stirrer, and finally, adding the protective agent to the drainage agent system, and continuously stirring during the adding process to ensure that the protective agent can be quickly and evenly dispersed in the entire system to achieve a comprehensive coverage and protection effect; S3.5. Continue the aging treatment at 45-75°C for 16-18h to ensure that the chemical reaction between the components is fully completed, and finally obtain the drainage agent for oil well fracturing.

[0017] Furthermore, the specific stirring speed of the stirrer in S3.3 is 150-200 rpm; the stirring time is 10-15 min; and the stirring temperature is 45-60°C; the specific stirring speed of the stirrer in S3.4 is 100-180 rpm; the stirring time is 20-30 min; and the stirring temperature is 45-55°C.

[0018] One or more technical solutions provided in the embodiments of the present application have at least the following technical effects or advantages: First, in CO 2In oil displacement technology, high temperature environment causes the performance of conventional coating material bisphenol A epoxy resin to decline, while the high temperature resistance of polytetrafluoroethylene enables it to maintain good stability and coating effect at high temperature, thereby improving the temperature resistance of the drainage agent. The high temperature resistant polytetrafluoroethylene coating layer ensures the stable performance of the drainage agent at high temperature and reduces the performance degradation caused by temperature changes; acrylic resin is used for pre-coating in the inner layer to form a solid resin layer, which enhances the bonding between quartz sand and the outer layer of polytetrafluoroethylene, prevents the coating layer from falling off under high temperature and high pressure, and further improves the stability and drainage effect of the drainage agent. The acrylic resin pre-coating layer enhances the bonding between quartz sand and the drainage agent, making The drainage agent can more effectively carry the proppant into the cracks during the fracturing process, and quickly return after the pressure is released, thereby improving the drainage effect; the double-layer packaging structure can prevent the sedimentation and agglomeration of quartz sand in the drainage agent, ensuring the uniformity and stability of the drainage agent; the fluidity and wear resistance of polytetrafluoroethylene help to reduce the friction resistance of the drainage agent during transportation and improve the transportation efficiency. The combination of acrylic resin and polytetrafluoroethylene provides good wettability and dispersibility for quartz sand, which can be better distributed in the drainage agent, improving the permeability and coverage of the drainage agent; during the fracturing process, the double-layer packaging structure can maintain the integrity and stability of the quartz sand and improve the compressive strength and durability of the proppant; Secondly, the polytetrafluoroethylene layer with low cross-linking density maintains good fluidity at room temperature, and can tightly wrap the inner layer of acrylic resin and quartz sand to form a smooth and wear-resistant outer layer; at higher temperatures, the polytetrafluoroethylene layer with low cross-linking density melts faster, promoting the rapid penetration and dispersion of the drainage agent at high temperatures; the inner layer of high cross-linking density acrylic resin layer and the outer layer of low cross-linking density polytetrafluoroethylene layer work together to improve the overall high temperature resistance of the drainage agent and ensure its effectiveness in high-temperature oil recovery operations; the acrylic resin with high cross-linking density melts slowly, the inner layer melts slowly to maintain structural integrity, and the outer layer of low cross-linking density polytetrafluoroethylene resin melts quickly, and the outer layer melts quickly to promote the rapid penetration and dispersion of the drainage agent at high temperatures, thereby improving the discharge rate and drainage rate; experimental data show that the discharge rate and drainage rate of Example 2 are increased to 72.3% and 85.7%, respectively, which are significantly improved compared with Example 1; The improved exhaust agent is not only suitable for CO 2 The high temperature environment in oil recovery technology can also be applied to other oil and gas extraction scenarios that require high temperature resistance, high stability and high discharge rate, improving the flexibility and adaptability of the use of drainage agents.

[0019] Third, through the combined use of large and small particle size quartz sand, a more compact filling structure can be formed. The large particle size quartz sand acts as a skeleton to provide stable support; the small particle size quartz sand is filled in the gaps between large particle size particles, reducing the porosity and improving the filling density; the addition of small particle size quartz sand increases the number of microchannels and pores inside the filler, which promotes the penetration and dispersion of the drainage agent at high temperature. The formation of microchannels improves the permeability of the filler, allowing the drainage agent to be more evenly distributed in the filler, thereby improving the drainage effect. Due to its large volume and weight, the large particle size quartz sand can play a stabilizing role in the filling structure. They are not easily washed or moved by the fluid, thereby maintaining the stability of the filling structure; the combined use of large and small particle size quartz sand enables the drainage agent to quickly penetrate into the surrounding medium at high temperature, improving the discharge rate and drainage rate; Fourth, the introduction of light calcium carbonate is particularly suitable for special scenarios such as fractured oil and gas reservoirs and low-pressure oil and gas reservoirs that require improved permeability and coverage. Its low density and good floating properties help the drainage agent to better penetrate into cracks and pores, thereby improving the drainage effect. The addition of light calcium carbonate not only increases the permeability and coverage of the drainage agent, but also may improve the adsorption and carrying capacity of the drainage agent through its porous structure and large specific surface area, further improving the discharge rate and drainage rate. By adjusting the addition ratio and particle size range of light calcium carbonate, the physical properties and drainage effects of the drainage agent can be flexibly controlled to adapt to different geological conditions and mining needs. DETAILED DESCRIPTION

[0020] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which the present invention belongs; the terms used in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention; the term "and / or" used herein includes any and all combinations of one or more related listed items.

[0021] Embodiment 1: A drainage agent for oil well fracturing, comprising the following components: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler prefabricated fluid; Wherein, the modified dispersant is a modified lignin obtained by sulfonating lignin with potassium bisulfite; The modified dispersant preparation method is as follows: S1.1, pre-treating lignin by alkali extraction to remove impurities, and dissolving the pre-treated lignin in 3% dilute sulfuric acid to obtain a lignin solution; S1.2, add 8 parts by weight of potassium bisulfite to 10 parts by weight of the lignin solution, stir at a temperature range of 60-90°C with a stirrer at a speed of 60-120 rpm for 20-35 minutes, and allow the potassium bisulfite to react with the lignin to achieve sulfonation modification; S1.3, after the reaction is completed, the mixture is cooled to room temperature, and then filtered, washed, and dried to remove the unreacted sulfite and other by-products to obtain a sulfonated lignin modified dispersant; The modified filler prefabricated liquid is prepared by coating and modifying quartz sand with polytetrafluoroethylene and acrylic resin; The preparation method of the modified filler prefabricated liquid is as follows: S2.1, mixing acrylic resin and ethanol in a volume ratio of 3:2, heating until the acrylic resin is molten, stirring evenly, to obtain a flowable acrylic resin solution; Disperse the pretreated quartz sand evenly into the acrylic resin solution, stir for 15-20 minutes at a temperature of 60-80°C and a stirring speed of 200-300rpm, so that the surface of the quartz sand is evenly coated with a layer of acrylic resin to form an inner solid resin coating layer; The coated quartz sand is filtered to remove excess acrylic resin solution, and then placed in an oven and dried at 80-100° C. to solidify the acrylic resin to obtain inner-layer coated quartz sand; The quartz sand pretreatment is specifically as follows: 3-aminopropyltriethoxysilane is dissolved in deionized water to obtain a 3-aminopropyltriethoxysilane solution with a concentration of 5%, and the quartz sand is poured into a stirrer containing the prepared 3-aminopropyltriethoxysilane solution, and stirred at 40-60° C. and 260-320 rpm for 2-3 hours. After the stirring is completed, the quartz sand is filtered and separated from the solution, and placed in an oven and dried at a temperature of 80-95° C. to completely remove moisture, thereby obtaining pretreated quartz sand; S2.2, mixing polytetrafluoroethylene and ethanol in a volume ratio of 3:2, and heating until the polytetrafluoroethylene is molten to prepare a flowable polytetrafluoroethylene solution; 10 parts by weight of the inner-layer coated quartz sand is uniformly dispersed into 25 parts by weight of the prepared polytetrafluoroethylene solution, and stirred for 15-20 minutes at a temperature of 65-80° C. and a stirring speed of 260-380 rpm by a stirrer, so that the quartz sand is uniformly dispersed in the polytetrafluoroethylene solution, and the quartz sand is fully wrapped and infiltrated by the polytetrafluoroethylene solution to obtain a modified filler prefabricated liquid; The base liquid is formed by mixing water and polyoxyethylene octylphenol ether emulsifier; Wherein, the mixing ratio of water and polyoxyethylene octylphenol ether emulsifier is 9:0.3-0.9; The viscosity modifier is any one of carboxymethyl cellulose or guar gum; The breaker is any one of quartz sand, ceramic particles or microspheres; The acidulant is a mixture of one or more of hydrochloric acid, hydrofluoric acid or earth acid; The protective agent is a mixture of one or more of butylated hydroxytoluene, isothiazolinone or silver ion antibacterial agent; A method for producing a drainage agent for oil well fracturing comprises the following steps: S3.1. According to the requirements of the content of each component in the formula of the oil well fracturing agent, weigh the following raw material components in percentage by weight: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler; S3.2, firstly mix the modified dispersant with the diethylenetriamine crosslinking agent, and stir them at a speed of 120-180rpm with a magnetic stirrer for 8-15min to ensure that the two are fully reacted to generate an amine-containing lignin derivative solution; then, mix the amine-containing lignin derivative solution with the modified filler prefabricated solution, and stir them at a temperature of 60-80°C with a magnetic stirrer at a speed of 120-160rpm for 15-30min to generate a lignin derivative solution with an amine functional group, and obtain a grafted blend; S3.3, according to the formula ratio in step S3.1, first add the base liquid into the stirrer, and stir it with the stirrer; at the same time, add the viscosity modifier into the base liquid, and continue to stir so that the viscosity modifier is evenly dispersed in the base liquid; then, under stirring, add the breaker and the acidifier in sequence, and continue to stir until the mixture is evenly mixed to prepare a mixture; The specific stirring speed of the stirrer is 150-200 rpm; the stirring time is 10-15 min; and the stirring temperature is 45-60°C.

[0022] S3.4, adding the grafted blend obtained in step S3.2 to the mixture, and evenly dispersing it in the entire drainage agent system by a stirrer, and finally, adding the protective agent to the drainage agent system, and continuously stirring during the adding process to ensure that the protective agent can be quickly and evenly dispersed in the entire system to achieve a comprehensive coverage and protection effect; The specific stirring speed of the stirrer is 100-180rpm; the stirring time is 20-30min; the stirring temperature is 45-55°C; S3.5. Continue the aging treatment at 45-75°C for 16-18h to ensure that the chemical reaction between the components is fully completed, and finally obtain the drainage agent for oil well fracturing.

[0023] The following experiment was conducted for this embodiment: according to the content requirements of each component in the formula of the oil well fracturing auxiliary agent, the following raw material components were weighed in mass percentage: 90 parts by weight of base fluid, 0.5 parts by weight of viscosity modifier, 3 parts by weight of breaker, 0.5 parts by weight of modified dispersant, 7 parts by weight of diethylenetriamine crosslinking agent, 1 part by weight of acidulant, 0.3 parts by weight of protective agent and 30 parts by weight of modified filler; First, the modified dispersant and the diethylenetriamine crosslinking agent are mixed, and stirred at a speed of 120-180 rpm using a magnetic stirrer for 8-15 minutes to ensure that the two are fully reacted to generate an amino-containing lignin derivative solution; Subsequently, the amine-containing lignin derivative solution is mixed with the modified filler pre-liquid, and stirred at 60-80° C. with a magnetic stirrer at 120-160 rpm for 15-30 minutes to generate a lignin derivative solution with an amine functional group, thereby obtaining a grafted blend; According to the weighed raw material components, the base liquid is first added into the stirrer, and the stirrer is stirred, wherein the stirrer is stirred at a temperature of 40-60° C. and a stirring speed of 120-200 rpm for 8-15 minutes; At the same time, a viscosity regulator is added to the base liquid, and the viscosity regulator is uniformly dispersed in the base liquid by continuous stirring; then, a breaker and an acidifier are added in sequence under stirring, and stirring is continued until the mixture is uniformly mixed to prepare a mixture; Add the grafted blend to the mixture and disperse it evenly in the entire drainage agent system by a stirrer, wherein the stirrer stirs at a stirring temperature of 45-55°C and a stirring speed of 90-180rpm for 15-30min; finally, add the protective agent to the drainage agent system, and continue stirring during the addition process to ensure that the protective agent can be quickly and evenly dispersed in the entire system to achieve a comprehensive coverage and protection effect; Continue to mature the mixture at 45-75°C for 16-18 hours to ensure that the chemical reaction between the components is fully completed, and finally obtain a drainage agent for oil well fracturing.

[0024] The comparative example is prepared by the method of patent application number CN202410407362.6, which is different from the present embodiment in that the modified filler prefabricated liquid is prepared by coating and modifying quartz sand with bisphenol A epoxy resin; The performance index inspection items and inspection standards are as follows: The specific test conditions, equipment and operation steps should strictly refer to SY / T 5755-2016 "Performance Evaluation Method of Discharge Aids for Fracturing Acidification" to conduct experimental tests on the discharge rate and drainage rate; Discharge rate test method: Discharge rate refers to the proportion of fluid discharged from the blocked formation by adding a drainage agent under specific conditions. Under laboratory conditions, a sand box is usually used to simulate the formation model for testing, and the discharge rate is determined by measuring the flow of the fluid before and after the addition of the drainage agent. Specifically, a sand box model containing a certain proportion of blocking material is prepared, the drainage agent to be tested is added to the sand box model according to the specified proportion, clean water or other reference fluid is injected, the outflow volume without the addition of the drainage agent is recorded, the same fluid is injected again, the outflow volume after the addition of the drainage agent is recorded, and the discharge rate is calculated. Drainage rate test method: refers to the ability of drainage aids in improving fluid drainage efficiency, which is evaluated by comparing the drainage rates before and after the addition of drainage aids. The test method of drainage rate is similar to the drainage rate, focusing on evaluating the effect of drainage agents on improving formation permeability. Specifically, prepare a sand box model containing a certain proportion of plugging material, add the drainage agent to be tested into the sand box model according to the specified proportion, repeat the drainage rate test under different conditions, record the data of each test, and calculate the corresponding drainage rate.

[0025] According to the above standards, the present embodiment and the comparative example were tested. After testing, the discharge rate of the drainage aid of the comparative example was 62.6%, and the drainage aid rate was 76.8%; the discharge rate of the drainage aid of the present embodiment was 68.5%, and the drainage aid rate was 82.3%.

[0026] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: After testing, the discharge rate of this solution increased from 62.6% to 68.5% compared with the control group, and the auxiliary discharge rate increased from 68.5% to 82.3%; 2 In oil displacement technology, high temperature environment causes the performance of conventional coating material bisphenol A epoxy resin to decline, while the high temperature resistance of polytetrafluoroethylene enables it to maintain good stability and coating effect at high temperature, thereby improving the temperature resistance of the drainage agent. The high temperature resistant polytetrafluoroethylene coating layer ensures the stable performance of the drainage agent at high temperature and reduces the performance degradation caused by temperature changes. Acrylic resin is used for pre-coating in the inner layer to form a solid resin layer, which enhances the bonding between quartz sand and the outer polytetrafluoroethylene layer, prevents the coating layer from falling off under high temperature and high pressure, and further improves the stability and drainage effect of the drainage agent. The acrylic resin pre-coating layer enhances the bonding between quartz sand and the drainage agent, so that the drainage agent can more effectively carry the proppant into the crack during the fracturing process and quickly return after the pressure is released, thereby improving the drainage effect. In CO 2In oil displacement technology, higher temperatures are usually required to enhance the oil displacement effect. Traditional bisphenol A epoxy resin will experience performance degradation at high temperatures, such as softening and decomposition, which will affect its coating effect and the overall performance of the drainage agent. Polytetrafluoroethylene has excellent high temperature resistance and can maintain stable chemical and physical properties at high temperatures. By replacing bisphenol A epoxy resin with polytetrafluoroethylene, the drainage agent can still maintain good stability and coating effect in a high temperature environment, thereby ensuring the effectiveness of the drainage agent in high-temperature oil displacement operations. It can maintain a fluid state at room temperature and can tightly wrap the inner layer of acrylic resin to form a smooth and wear-resistant outer layer, further enhancing the mechanical strength and stability of the overall structure. The outer layer of polytetrafluoroethylene can still maintain stable chemical properties and good fluidity at high temperatures, ensuring the effective wrapping and dispersion of quartz sand in a high temperature environment. The addition of acrylic resin pre-coating layer provides a solid inner layer of resin protection for quartz sand, which remains solid at low temperature, provides effective protection and support for quartz sand, and prevents it from being damaged during transportation and handling. This pre-coating layer can not only enhance the bonding strength between quartz sand and the outer layer of polytetrafluoroethylene, but also prevent the coating layer from falling off or being damaged under high temperature and high pressure, thereby enhancing the stability and durability of the entire coating layer, so that the drainage aid can maintain its performance for a longer time in a complex underground environment, and improve the durability of the drainage aid effect; as the temperature rises, the inner layer of acrylic resin gradually softens or even partially melts, but it still maintains a certain structural strength, providing continuous protection for the quartz sand; The double-layer wrapping structure can prevent the sedimentation and agglomeration of quartz sand in the drainage agent, ensuring the uniformity and stability of the drainage agent; the fluidity and wear resistance of polytetrafluoroethylene help reduce the friction resistance of the drainage agent during transportation and improve the transportation efficiency. The combination of acrylic resin and polytetrafluoroethylene provides good wettability and dispersibility for quartz sand, which can be better distributed in the drainage agent, improving the permeability and coverage of the drainage agent; during the fracturing process, the double-layer wrapping structure can maintain the integrity and stability of the quartz sand and improve the compressive strength and durability of the proppant; The improved drainage agent has better high temperature resistance and a more stable coating layer. The double-layer coating structure can reduce the retention and adsorption of quartz sand in the drainage agent, reduce the damage to the reservoir permeability, and can more effectively carry the proppant into the cracks during high-temperature oil recovery operations, and quickly return after the pressure is released, reducing the problems of formation blockage and drainage agent residue. At the same time, the low surface energy characteristics of polytetrafluoroethylene can also reduce the adhesion between the drainage agent and the formation rock, further promoting the discharge of liquid; the drainage rate and drainage rate of the drainage agent are improved, thereby improving the production and mining efficiency of oil and gas wells; Due to the high temperature resistance of polytetrafluoroethylene and the strengthening effect of acrylic resin, the improved exhaust agent is not only suitable for CO 2The high temperature environment in oil recovery technology may also be applicable to other oil and gas production scenarios that require high-temperature resistant drainage agents, thereby expanding the scope of application of drainage agents.

[0027] Example 2: The above-mentioned Example 1 uses polytetrafluoroethylene and acrylic resin to coat quartz sand to form a double-layer coating structure with a solid inner layer and a flowing outer layer, thereby enhancing the mechanical strength, stability and high temperature resistance of the drainage agent, and improving the discharge rate and drainage rate of the drainage agent. In order to further improve the discharge rate and drainage rate of the drainage agent, further improvements are made on the basis of Example 1.

[0028] In the preparation of the modified filler preform, the reactions of S2.1 and S2.2 are adjusted, specifically: In S2.1, diethylenetriamine is added to the acrylic resin solution as a crosslinking agent, wherein the amount of the diethylenetriamine crosslinking agent is 8%-10% by weight of the acrylic resin; In S2.2, when coating with the polytetrafluoroethylene solution, the mixture is stirred at a temperature of 60-65° C. and a stirring speed of 200-260 rpm for 10-15 minutes.

[0029] The following experiment was conducted for this embodiment based on the experiment of the embodiment 1: the difference from the embodiment 1 is that when preparing the modified filler prefabricated liquid, in step S2.1, diethylenetriamine is added to the acrylic resin solution as a crosslinking agent, wherein the amount of the diethylenetriamine crosslinking agent is 9% of the weight of the acrylic resin; in step S2.2, the mixture is stirred at a temperature of 60-65° C. and a stirring speed of 200-260 rpm for 10-15 min by a stirrer; After testing, the discharge rate of the drainage aid in this embodiment is 72.3%, and the drainage aid rate is 85.7%.

[0030] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: In the process of preparing the modified filler prefabricated liquid, the crosslinking density of the resin is changed by changing the dosage of acrylic acid and polytetrafluoroethylene crosslinking agent and the crosslinking reaction conditions, thereby preparing a resin with a high crosslinking density in the inner layer and a resin with a low crosslinking density in the outer layer. The acrylic resin layer with a high crosslinking density has higher mechanical strength and chemical resistance, and can provide a stronger inner layer protection for the quartz sand. At the same time, the high crosslinking density makes the inner layer of acrylic resin melt more slowly at a higher temperature, and can maintain the structural integrity and stability for a longer time. The low cross-link density polytetrafluoroethylene layer maintains good fluidity at room temperature and can tightly wrap the inner layer of acrylic resin and quartz sand to form a smooth and wear-resistant outer layer; at higher temperatures, the low cross-link density polytetrafluoroethylene layer melts faster, promoting the rapid penetration and dispersion of the drainage agent at high temperatures; the inner layer of high cross-link density acrylic resin layer and the outer layer of low cross-link density polytetrafluoroethylene layer work together to improve the overall high temperature resistance of the drainage agent and ensure its effectiveness in high temperature oil displacement operations; The inner layer of acrylic resin with high cross-linking density melts slowly, and the slow melting of the inner layer maintains the structural integrity. The outer layer of polytetrafluoroethylene resin with low cross-linking density melts quickly, and the rapid melting of the outer layer promotes the rapid penetration and dispersion of the drainage aid at high temperature, thereby improving the drainage rate and drainage aid rate. Experimental data show that the drainage rate and drainage aid rate of Example 2 are increased to 72.3% and 85.7% respectively, which are significantly improved compared with Example 1. The improved exhaust agent is not only suitable for CO 2 The high temperature environment in oil recovery technology can also be applied to other oil and gas extraction scenarios that require high temperature resistance, high stability and high discharge rate, improving the flexibility and adaptability of the use of drainage agents.

[0031] Example 3: The above-mentioned Example 2 achieves slow melting of the inner layer to maintain structural integrity and fast melting of the outer layer to promote rapid penetration and dispersion of the drainage agent at high temperature, thereby improving the drainage rate and drainage efficiency of the drainage agent. In order to further improve the drainage rate and drainage efficiency of the drainage agent, further improvements are made on the basis of Example 2.

[0032] In the preparation of the modified filler prefabricated liquid, the particle size of the quartz sand also includes large particle size and small particle size, wherein the particle size range of the large particle size is 0.42-1mm; the small particle size is 0.10-0.25mm; and the weight ratio of the large particle size to the small particle size is (1-2):1.

[0033] The following experiment was conducted on this embodiment based on the experiment of the second embodiment: the difference from the second embodiment is that the quartz sand also includes two types of large particle size and small particle size, wherein the particle size range of the large particle size is 0.42-1mm; the small particle size is 0.10-0.25mm; the weight ratio of the large particle size to the small particle size is 1.5:1; After testing, the discharge rate of the drainage aid in this embodiment is 76.1%, and the drainage aid rate is 88.6%.

[0034] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: By introducing quartz sand with large particle size of 0.42-1mm and small particle size of 0.10-0.25mm and mixing them in a certain weight ratio, the structure of the filler is optimized by utilizing the gaps and arrangement between particles of different particle sizes; the mixed use of large particle size and small particle size quartz sand increases the contact area and the number of interfaces between particles, thereby forming more microchannels and micropores, and these microstructures can more effectively promote the penetration and dispersion of the drainage agent at high temperature; during the coating process, the difference in the melting rate of the inner and outer layers of quartz sand with different particle sizes is further increased due to the difference in their specific surface area and volume; the inner layer of large particle size quartz sand has a thicker coating layer and melts slowly, so it can maintain structural integrity; while the outer layer of small particle size quartz sand has a thinner coating layer and melts quickly, which promotes the rapid release of the drainage agent; The combined use of large and small particle size quartz sand can form a more compact filling structure. The large particle size quartz sand acts as a skeleton and provides stable support. The small particle size quartz sand is filled in the gaps between large particle size particles, reducing the porosity and improving the filling density. The addition of small particle size quartz sand increases the number of microchannels and pores inside the filler, which promotes the penetration and dispersion of the drainage agent at high temperature. The formation of microchannels improves the permeability of the filler, allowing the drainage agent to be more evenly distributed in the filler, thereby improving the drainage effect. Due to its large volume and weight, the large particle size quartz sand can play a stabilizing role in the filling structure. They are not easily washed or moved by the fluid, thereby maintaining the stability of the filling structure. The combined use of large and small particle size quartz sand enables the drainage agent to quickly penetrate into the surrounding medium at high temperature, improving the discharge rate and drainage rate. Due to the structural optimization and the formation of microchannels, the drainage agent can pass through the gaps between particles more smoothly during the melting process, thereby improving the drainage rate of the drainage agent. The rapid penetration and dispersion of the drainage agent at high temperature makes it more fully in contact with the surrounding medium, thereby playing a more effective drainage role. Experimental data show that the drainage rate has increased to 76.1% and the drainage rate has increased to 88.6%. The slow melting of the large-particle quartz sand in the inner layer can maintain the stability of the overall structure and avoid structural collapse or premature loss of the drainage agent due to rapid melting. By using two particle sizes in combination, the discharge rate and drainage rate of the drainage aid are increased, thereby improving the performance of the overall product and further expanding the scope of use.

[0035] Example 4: The above-mentioned Example 3 achieves structural optimization and the formation of microchannels through the combined use of large and small particle size quartz sand. The drainage agent can pass through the gaps between the particles more smoothly during the melting process, thereby improving the discharge rate and drainage rate of the drainage agent. In order to further improve the discharge rate and drainage rate of the drainage agent, further improvements are made on the basis of Example 3.

[0036] The modified filler also includes light calcium carbonate, the particle size of which is 0.8-0.15 mm and the density is 0.5 g / cm³; the light calcium carbonate accounts for 12%-18% of the total weight of the modified filler; In step S2.2, light calcium carbonate accounting for 12%-18% of the total weight of the modified filler is added to the flowable polytetrafluoroethylene solution.

[0037] The following experiment was conducted for this embodiment based on the experiment of the third embodiment: The difference between this embodiment and the third embodiment is that in step S2.2, light calcium carbonate accounting for 15% of the total weight of the modified filler is added to the flowable polytetrafluoroethylene solution; After testing, the discharge rate of this embodiment is 76.9%, and the auxiliary discharge rate is 89.4%.

[0038] The technical solutions in the above embodiments of the present application have at least the following technical effects or advantages: The introduction of light calcium carbonate is particularly suitable for special scenarios such as fractured oil and gas reservoirs and low-pressure oil and gas reservoirs that require improved permeability and coverage. Its low density and good floating performance help the drainage agent to better penetrate into the cracks and pores, thereby improving the drainage effect. The addition of light calcium carbonate not only increases the permeability and coverage of the drainage agent, but also may improve the adsorption and carrying capacity of the drainage agent through its porous structure and large specific surface area, further improving the drainage rate and drainage efficiency. By adjusting the addition ratio and particle size range of light calcium carbonate, the physical properties and drainage effect of the drainage agent can be flexibly controlled to adapt to different geological conditions and mining needs. The density of light calcium carbonate is much lower than that of quartz sand. This density difference makes light calcium carbonate particles have good floating performance in drainage agents. In special scenarios such as fractured oil and gas reservoirs and low-pressure oil and gas reservoirs, light calcium carbonate can carry drainage agents to better penetrate into cracks and pores, improving the coverage and permeability of drainage agents. The addition of light calcium carbonate particles, together with quartz sand particles, forms more microchannels and micropores in the drainage agent. These microstructures help the drainage agent to pass through the gaps between particles more smoothly during the melting process, improving the discharge rate and drainage efficiency. The porous structure and large specific surface area of ​​light calcium carbonate increase the contact area between the drainage agent and the formation rock, and improve the adsorption and carrying capacity of the drainage agent. It promotes the drainage agent to carry the proppant into the fracture more effectively and quickly return after the pressure is released. The low density and good floating performance of light calcium carbonate enable it to carry drainage aids to penetrate deeper cracks and pores, significantly improving the permeability and coverage of drainage aids, and is suitable for special environments such as fractured oil and gas reservoirs and low-pressure oil and gas reservoirs; the addition of light calcium carbonate and quartz sand particles together form more microchannels and micropores, allowing the drainage aid to pass through the gaps between particles more smoothly during the melting process. At the same time, the porous structure and large specific surface area of ​​light calcium carbonate improve the adsorption and carrying capacity of the drainage aid, thereby further improving the discharge rate and drainage rate; the introduction of light calcium carbonate does not weaken the overall stability and durability of the modified filler. Light calcium carbonate forms a close combination with components such as polytetrafluoroethylene and acrylic resin, ensuring the stability and durability of the drainage aid in harsh environments such as high temperature and high pressure; by adjusting the addition ratio and particle size range of light calcium carbonate, the physical properties and drainage effect of the drainage agent can be flexibly controlled. This enables the drainage agent to better adapt to different geological conditions and mining needs, and improves its applicability and effectiveness in various scenarios.

[0039] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A drainage agent for oil well fracturing, characterized in that: The invention comprises the following components: 80-95 parts by weight of base liquid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of cracking agent, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler prefabricated liquid; Wherein, the modified dispersant is a modified lignin obtained by sulfonating lignin with potassium bisulfite; The modified filler prefabricated liquid is prepared by coating and modifying quartz sand with polytetrafluoroethylene and acrylic resin; The base liquid is formed by mixing water and polyoxyethylene octylphenol ether emulsifier; Wherein, the mixing ratio of water and polyoxyethylene octylphenol ether emulsifier is 9:0.3-0.9; The viscosity modifier is any one of carboxymethyl cellulose or guar gum; The breaker is any one of quartz sand, ceramic particles or microspheres; The acidulant is a mixture of one or more of hydrochloric acid, hydrofluoric acid or earth acid; The protective agent is one or more mixtures of butylated hydroxytoluene, isothiazolinone or silver ion antibacterial agent.

2. The oil well fracturing drainage agent according to claim 1, characterized in that: The preparation method of the modified filler prefabricated liquid is as follows: S2.1, mixing acrylic resin and ethanol in a volume ratio of 3:2, heating until the acrylic resin is molten, stirring evenly, to obtain a flowable acrylic resin solution; Disperse the pretreated quartz sand evenly into the acrylic resin solution, stir for 15-20 minutes at a temperature of 60-80°C and a stirring speed of 200-300rpm, so that the surface of the quartz sand is evenly coated with a layer of acrylic resin to form an inner solid resin coating layer; The coated quartz sand is filtered to remove excess acrylic resin solution, and then placed in an oven and dried at 80-100° C. to solidify the acrylic resin to obtain inner-layer coated quartz sand; S2.2, mixing polytetrafluoroethylene and ethanol in a volume ratio of 3:2, and heating until the polytetrafluoroethylene is molten to prepare a flowable polytetrafluoroethylene solution; 10 parts by weight of the inner-layer coated quartz sand are evenly dispersed into 25 parts by weight of the prepared polytetrafluoroethylene solution, and stirred for 15-20 minutes at a temperature of 65-80°C with a stirring speed of 260-380 rpm by a stirrer to evenly disperse the quartz sand in the polytetrafluoroethylene solution, so that the quartz sand is fully wrapped and infiltrated by the polytetrafluoroethylene solution to obtain a modified filler prefabricated liquid.

3. The oil well fracturing drainage agent according to claim 2, characterized in that: In the preparation of the modified filler preform, the reactions of S2.1 and S2.2 are adjusted, specifically: In S2.1, diethylenetriamine is added to the acrylic resin solution as a crosslinking agent, wherein the amount of the diethylenetriamine crosslinking agent is 8%-10% by weight of the acrylic resin; In S2.2, when coating with the polytetrafluoroethylene solution, the mixture is stirred at a temperature of 60-65° C. and a stirring speed of 200-260 rpm for 10-15 minutes.

4. The oil well fracturing drainage agent according to claim 3, characterized in that: The particle size of quartz sand in the modified filler also includes large particle size and small particle size.

5. The oil well fracturing drainage agent according to claim 4, characterized in that: The particle size range of large particles is 0.42-1mm; the small particle size is 0.10-0.25mm; the weight ratio of large particle size to small particle size is (1-2):

1.

6. The oil well fracturing drainage agent according to claim 4, characterized in that: Modified fillers also include light calcium carbonate.

7. The oil well fracturing drainage agent according to claim 6, characterized in that: The light calcium carbonate has a particle size of 0.8-0.15 mm and a density of 0.5 g / cm³.

8. The oil well fracturing drainage agent according to claim 6, characterized in that: The light calcium carbonate accounts for 12%-18% of the total weight of the modified filler.

9. A method for producing a drainage aid for oil well fracturing according to any one of claims 1 to 8, characterized in that: The specific steps include: S3.

1. According to the requirements of the content of each component in the formula of the oil well fracturing agent, weigh the following raw material components in percentage by weight: 80-95 parts by weight of base fluid, 0.3-0.9 parts by weight of viscosity modifier, 3-5 parts by weight of breaker, 0.2-0.5 parts by weight of modified dispersant, 6-8 parts by weight of diethylenetriamine crosslinking agent, 1-3 parts by weight of acidulant, 0.3-0.6 parts by weight of protective agent and 10-30 parts by weight of modified filler; S3.2, firstly mix the modified dispersant with the diethylenetriamine crosslinking agent, and stir them at a speed of 120-180rpm with a magnetic stirrer for 8-15min to ensure that the two are fully reacted to generate an amine-containing lignin derivative solution; then, mix the amine-containing lignin derivative solution with the modified filler prefabricated solution, and stir them at a temperature of 60-80°C with a magnetic stirrer at a speed of 120-160rpm for 15-30min to generate a lignin derivative solution with an amine functional group, and obtain a grafted blend; S3.3, according to the formula ratio in step S3.1, first add the base liquid into the stirrer, and stir it with the stirrer; at the same time, add the viscosity modifier into the base liquid, and continue to stir so that the viscosity modifier is evenly dispersed in the base liquid; then, under stirring, add the breaker and the acidifier in sequence, and continue to stir until the mixture is evenly mixed to prepare a mixture; S3.4, adding the grafted blend obtained in step S3.2 to the mixture, and evenly dispersing it in the entire drainage agent system by a stirrer, and finally, adding the protective agent to the drainage agent system, and continuously stirring during the adding process to ensure that the protective agent can be quickly and evenly dispersed in the entire system to achieve a comprehensive coverage and protection effect; S3.

5. Continue the aging treatment at 45-75°C for 16-18h to ensure that the chemical reaction between the components is fully completed, and finally obtain the drainage agent for oil well fracturing.

10. The method for producing a drainage aid for oil well fracturing according to claim 9, characterized in that: The specific stirring speed of the stirrer in S3.3 is 150-200 rpm; the stirring time is 10-15 min; and the stirring temperature is 45-60°C; the specific stirring speed of the stirrer in S3.4 is 100-180 rpm; the stirring time is 20-30 min; and the stirring temperature is 45-55°C.

Citation Information

Patent Citations

  • A drainage aid for oil well fracturing and production method

    CN117987134B